2017
DOI: 10.1002/ejoc.201601103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thiazolidine‐2‐thiones through a One‐Pot A3‐Coupling–Carbon Disulfide Incorporation Process

Abstract: A copper‐catalyzed two‐step one‐pot procedure for the synthesis of thiazolidine‐2‐thiones has been developed. The process involves a three‐component coupling of an alkyne, an aldehyde, and an amine (A3‐coupling) followed by trapping the resulting propargylamine with carbon disulfide and subsequent cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Many synthetic methods have been developed for the synthesis of different classes of heterocycles [1][2][3][4][5][6][7][8][9][10] starting from propargylamines. At the same time, propargylamines are direct precursors of propargylureas that can undergo silver-or gold-catalyzed cycloisomerization to produce a series of other nitrogen-containing heterocyclic compounds.…”
mentioning
confidence: 99%
“…Many synthetic methods have been developed for the synthesis of different classes of heterocycles [1][2][3][4][5][6][7][8][9][10] starting from propargylamines. At the same time, propargylamines are direct precursors of propargylureas that can undergo silver-or gold-catalyzed cycloisomerization to produce a series of other nitrogen-containing heterocyclic compounds.…”
mentioning
confidence: 99%
“…Three anhydrous additives, MgSO 4 , Na 2 SO 4 and 3 Å MS, were attempted (entries 10-12), and Na 2 SO 4 provided 90 % ee value (entry 11). We investigated the affection of reaction temperature and time (compare entries 9, [13][14][15][16][17], and found that 60°C and 12 h were suitable (entry 16). Other solvents were attempted, and the results showed that toluene was optimal (see Table S1).…”
Section: Optimization Of Conditions For the Synthesis Of Chiral Propargylaminesmentioning
confidence: 99%
“…[5] The reactions with propargylamines as the substrates can provide miscellaneous heterocyclic compounds [6] such as pyrroles, [7] pyrrolines, [8] pyrrolidine, [9] pyrazines, [10] pyrazoles, [11] pyridines, [12] dihydropyridines, [13] isoxazoles, [14] oxazolidines, [15] thiazoles [16] and thiazolidines. [17] The common methods for synthesis of chiral propargylamines include the asymmetric alkynylation of imines [18,19] and the catalytic asymmetric addition of nucleophiles to previously prepared [20] or in situ generated [21,22] Calkynyl imines (Scheme 1a). In 2016, Shao and co-workers reported the catalytic asymmetric arylations of C-alkynyl imines leading to chiral propargylamines with C-alkynyl N-Boc-protected N,O-acetals and phenols as the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Van der Eycken and co‐workers developed a Cu(I)‐catalyzed one‐pot two‐step procedure for the synthesis of thiazolidine‐2‐thiones from primary amines 1 p , aldehydes 2 , alkynes 3 , and carbon disulfide (Scheme 34). [79] The in situ generated propargylamines 4 were shown to react with CS 2 in the presence of 15 mol% CuBr in toluene at 100 °C to form thiazolidine‐2‐thiones 127 . A plausible mechanism for this transformation includes formation of carbamodithioic acid intermediate 128 undergoing 5‐exo‐dig cyclization via attack of the sulfur center at the triple bond.…”
Section: Synthesis Of Five‐membered Nos‐heterocyclesmentioning
confidence: 99%